Proteção de dados no contrato de plano de saúde: aspectos jurídicos da LGPD na experiência do consumidor - Almeida, Gustavo Palheiro Mendes de (2021)
This master's dissertation aims to present some legal aspects of the General Personal Data Protection Law related to health insurance. This Law circumscribes a series of rules that protect personal data and affects almost all economic sectors. The health insurance sector plays a relevant social role in order to avoid or mitigate financial losses in the event of illness and occupies a prominent place related to the Law impacts because it needs to process sensitive data as an input for its activity. Therefore, all health insurance contracts must comply with the new legislation to provide a consumer experience in accordance with the new personal data protection rights incorporated into Brazilian legal system.